Retrospective Study: Candidiasis Vulvovaginalis in Human Immunodeficiency Virus (HIV) and Acquired Immunodeficiency Syndrome (AIDS) Infection Patient - Sari, Diana Kartika; MurtiastutikDepartemen, Dwi (Faculty Of Medicine Airlangga University, 2015)
Background: Candidiasis vulvovaginal is an opportunistic fungal infection. The case of candidiasis vulvovaginalis increases in women with Human immunodeficiency virus (HIV) infection mainly with moderate to severe immunocompromised state. Purpose: To evaluate general feature of candidiasis vulvovaginalis in HIV and acquired immunodeficiency syndrome (AIDS) patient in Outpatient Clinic of Intermediate Care of Infection Disease, Dr. Soetomo General Hospital Surabaya. Methods: Retrospective study of candidiasis vulvovaginalis in HIV and AIDS patients on outpatient UPIPI Instalation Dr. Soetomo General ndthHospital Surabaya during January 2 2009 until Desember 30 2011. Data was taken from medical records. Results: The highest number of new candidiasis vulvovaginalis patient visit was in 2011. Seven patients underwent wet mount and gram examination, all showed positive results. The highest CD4+ examination results are < 200. All patients received ketoconazole treatment. Three patients came back for follow up and having complete healing. Conclusions: Number of candidiasis vulvovaginalis in HIV and AIDS infection cases per year were 5-7 patients. Diagnosis of candidiasis vulvovaginalis was based on patient complaints, physical, and laboratory examinations.Key words: vulvovaginal candidasis, HIV, AIDS.